2022
DOI: 10.1007/s00402-022-04482-6
|View full text |Cite
|
Sign up to set email alerts
|

Posterior shoulder dislocation with associated reverse Hill–Sachs lesion: clinical outcome 10 years after joint-preserving surgery

Abstract: Introduction Posterior shoulder dislocation in association with reverse Hill–Sachs lesion is a rather rare injury. Few studies reporting results after joint-preserving surgery in these cases are available. This current study presents the clinical outcomes 10 years postoperatively. Materials and methods In a prospective case series, we operatively treated 12 consecutive patients (all males) after posterior shoulder dislocation with associated reverse Hill–S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Pre-operative UCLA score was reported in four studies and its weighted average was 15.7 (7.8-25.8) [21,26,31,32]. The post-operative weighted average UCLA was found to be 27.4 ± 5.2 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and was reported in five studies [21,26,29,31,32].…”
Section: Overall Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Pre-operative UCLA score was reported in four studies and its weighted average was 15.7 (7.8-25.8) [21,26,31,32]. The post-operative weighted average UCLA was found to be 27.4 ± 5.2 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and was reported in five studies [21,26,29,31,32].…”
Section: Overall Resultsmentioning
confidence: 92%
“…Only three studies reported the pre-operative CMS with a mean value of 29 points [5,26,33]. The weighted average CMS found at the post-operative clinical evaluation was 79.4 (59-94) and was reported in 9 studies [5,8,[22][23][24][26][27][28]33]. Joint replacement procedures [28] and rotational osteotomy associated with ML procedure [24] reported the lowest post-operative scores, respectively, 59.5 and 59.…”
Section: Overall Resultsmentioning
confidence: 99%
See 3 more Smart Citations